INTEGRATED FINANCIAL MANAGEMENT INFORMATION SYSTEM IMPLEMENTATION AND ITS IMPACT ON PROCUREMENT PERFORMANCE AMONG PARASTATALS IN KENYA - Justus, Agnes Mutheu; Ndeto, Dr. Charles (International Journal of Supply Chain and Logistics, 2019)
Purpose: The purpose of the study was to assess IFMIS implementation and its impact on procurement performance among parastatals in Kenya with an aim of making recommendations on proper use of IFMIS. Methodology: This study adopted a descriptive research design approach targeting heads of procurement and ICT at the 187 parastatals. The study preferred this method because it allowed an in-depth study of the subject. To gather data, structured questionnaire were used to collect data from a sample of one hundred and thirty (130) respondents, who were selected using simple random sampling, from the four strata. Once collected, data was analyzed using descriptive and inferential statistics. Quantitative data was analyzed using multiple regression analysis. The qualitative data generated was analyzed by use of Statistical Package of Social Sciences (SPSS) version 22. Results: The response rate of the study was 74%. The regression results revealed that the IFMIS platforms identified in the study, that is, online inventory management, electronic vendor evaluation, online payments and online contract management combined could explain approximately 71.5% of the variations in the procurement performance among parastatals. The other 28.5% may be attributed to other strategies not explained by the model or the variables. Conclusion: The findings of the study indicated that online inventory management, electronic vendor evaluation, online payments and online contract management have a positive relationship with procurement performance among parastatals in Kenya. Contribution to theory, policy and practice: The study recommended that public institutions should embrace IFMIS technology so as to improve performance and further researches should to be carried out in other public institutions to find out if the same results can be obtained.